1996
DOI: 10.1136/pgmj.72.843.41
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis and rapidly progressive glomerulonephritis in the elderly

Abstract: SummaryThe proportion of patients with vasculitis and rapidly progressive nephritis aged 70 years or over has risen from about 10% in the 1980s to over 30% in series reported in the 1990s. This study was undertaken to examine the presentation and outcome of such older patients. Seventeen of 56 patients (30%) who presented at two renal units were aged 70 years or over. Mean creatinine level at presentation was 530 ytmol/l, and five patients received dialysis at presentation. Outcome was dependent on three facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A previous retrospective study by our group showed that patients aged 65 years or older who were diagnosed as having systemic necrotizing vasculitis (SNV; polyarteritis nodosa [PAN], granulomatosis with polyangiitis [Wegener's] [GPA], microscopic polyangiitis [MPA], or eosinophilic GPA [Churg‐Strauss] [EGPA]) had poorer outcomes than their younger counterparts, mainly because they developed more frequent and/or serious adverse events (SAEs; 68% versus 13%) while receiving conventional therapy . Several other groups have reported similar findings . Therefore, it is a common recommendation or practice to diminish, by up to one‐third, the dose of the most potent induction immunosuppressant, e.g., cyclophosphamide (CYC), for patients aged 65 years or older .…”
mentioning
confidence: 82%
“…A previous retrospective study by our group showed that patients aged 65 years or older who were diagnosed as having systemic necrotizing vasculitis (SNV; polyarteritis nodosa [PAN], granulomatosis with polyangiitis [Wegener's] [GPA], microscopic polyangiitis [MPA], or eosinophilic GPA [Churg‐Strauss] [EGPA]) had poorer outcomes than their younger counterparts, mainly because they developed more frequent and/or serious adverse events (SAEs; 68% versus 13%) while receiving conventional therapy . Several other groups have reported similar findings . Therefore, it is a common recommendation or practice to diminish, by up to one‐third, the dose of the most potent induction immunosuppressant, e.g., cyclophosphamide (CYC), for patients aged 65 years or older .…”
mentioning
confidence: 82%
“…As already reported in old people [2,[4][5][6][7], steroid and immunosuppressive treatments were effective in VS manifestations, but these treatments did not seem to influence the overall poor prognosis. The chosen therapy was adapted to each patient's status and was not directly the cause of death.…”
Section: Discussionmentioning
confidence: 53%
“…Published studies report a mortality rate of between 40 and 60% at 1-to 7-year follow-up in the elderly [2][3][4][5]. The main reported causes of death are complications due to infections and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 22% of patients with MPA who were registered in the Japanese Ministry of Health, Labour and Welfare of Japan database from 2006 to 2008 were treated with cyclophosphamide combined with corticosteroids . Previous reports have described avoiding the serious adverse events of immunosuppressants in the elderly AAV patients, and MPA patients were older than other AAV patients . However, the lower rate of using immunosuppressants may cause the high mortality.…”
Section: Discussionmentioning
confidence: 99%